Center commissioned external review of the Environment and Production Technology Division (EPTD) - Balisacan, Arsenio; Petit, Michel (International Food Policy Research Institute, 2008)
The CCER took place at IFPRI Headquarters in Washington DC from October 27 to 31, 2008. It was preceded by the reading of various documents provided to us by IFPRI, visits of the IFPRI website and anecdotal conversations with various people, knowledgeable about the work of the Division whom we happened to meet or talk to in the weeks preceding our visit to Washington. In addition, our assessment was based on presentations made to us by the Division Director and Division staff, group discussion with staff working on the three main themes of the Division’s agenda, further readings and telephone interviews with a small number of partners and donors. (See Appendix 1: Agenda.) Obviously, the sample of persons contacted was very small and should not be viewed as representative in any way. All of this limits the base of information for our assessment, which remains somewhat subjective as a result. But we should stress that we found a great degree of convergence among our various sources of information and that we easily agreed between the two of us on the main messages to convey in this report. We should also note that, in finalizing this report, we have taken into account the comments received during the presentation of our results to the Division staff, as well as the subsequent written comment from the Division Director. These have helped clarify our initial observations on some issues, especially those relating to capacity building and partnerships. Our Terms of Reference (see Appendix 2) were very broad. We focused mainly on the relevance and the quality of the Division’s work, looking at past activities and future plans. Our main desire is that our assessment will help the Division in the elaboration of its strategy for the future.